High temperature microcompression and nanoindentation in vacuum - Korte, Sandra; Stearn, Robert J.; Wheeler, Jeffrey M.; Clegg, William J. (Journal of Materials Research, 2012)
In small-scale testing at elevated temperatures, impurities in inert gases can pose problems so that testing in vacuum would be desirable. However, previous experiments have indicated difficulties with thermal stability and instrument noise. To investigate this, measurements of the temperature changes in a modified nanoindenter have been made and their influence on the displacement and load measurements is discussed. It is shown that controlling the temperatures of the indenter tip and the sample enabled flat punch indentations of gold, a good thermal conductor, to be carried out over several minutes at 665 °C in vacuum, as well as permitting thermal stability to be quickly re-established in site-specific microcompression experiments. This allowed compression of nickel superalloy micropillars up to sample temperatures of 630 °C with very low levels of oxidation after 48 h. Furthermore, the measured Young moduli, yield and flow stresses were consistent with literature data. © 2011 Materials Research Society.
Created from Fastlane, Scopus look-up
Keywords: Au; Nanoindentation; Stress/strain relationship